Doctoral Student Experiences in Indonesian Postgraduate Programs: A Phenomenological Investigation of Challenges - Evita Yuliatul Wahidah; Sangkot Sirait; Erika Setyanti Kusumaputri (STAI Hubbulwathan Duri, 2023)
This research answers academic anxiety that departs from a study of the complexity of the problems faced by doctoral students in Indonesia. The existing phenomenon is that doctoral students in Indonesia who are scattered in various public and private universities with various fields of knowledge still face many technical and non-technical problems caused by problems that are both academic and non-academic in nature. This research uses a qualitative descriptive approach with the phenomenological study method developed by Edmund Husserl. Data collection techniques use literature and field studies through interviews, documentation and observation. The primary data source is postgraduate students, and the secondary data source is the Postgraduate Director, Head of Study Program and administrative staff. Data analysis in this qualitative research consists of three streams of activities that occur simultaneously, namely data reduction, data presentation, drawing conclusions or verification. Data checking in this research is based on four criteria, namely, degree of trustworthiness, transferability, dependability, and certainty. The findings from this study include the theoretical level regarding the conceptualization of the Portrait of Doctoral Programs in Indonesia as an Educational Phenomenon and dissertation as Research Identity of Doctoral Programs (Standards and Characteristics). This research also found academic and non-academic problems for doctoral students in Indonesia. The implications of the results of this research are to provide recommendations for ideas for the academic community for making decisions and academic policies as well as formulating a quality education system and improving the quality assurance of postgraduate doctoral education in Indonesia.